Dilemmas and future perspectives of teachers in master fellowship program in education - Luis Sime Poma (Pontificia Universidad Católica del Perú, 2017)
Different fellowships programs to public school teachers have been developed in Latin-American. In Perú, this new program has been managed by Pronabec financing fellowships for teachers of different regions during 2014-2015. This study is addressed to analyze the teachers´ dilemmas faced when they applied; and, explore the future professional perspectives of this kind of teacher. The qualitative  method implies a documental analysis and survey with open answers to 20 teachers. Four types of dilemmas were identified-master versus family, master versus school, master versus another study, master versus no migration-, and eight possible futures scenarios related to the professional, academic, and unionpolitical fields.